2005
DOI: 10.1007/s00436-005-1476-6
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Giardia lamblia to Hovenia dulcis extracts

Abstract: Giardia lamblia is the causative agent of giardiasis, a common parasitic infection of the human and animal digestive tract. Although several drugs have been available to treat this infection, they present unpleasant side effects or cytotoxicity. In order to find a more natural treatment for the disease, we analyzed the effects of the methanolic extract and three fractions obtained from Hovenia dulcis Thunb. (Rhamnaceae) leaves on G. lamblia. Comparing all fractions, dichloromethane was more efficient in reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
0
22
0
2
Order By: Relevance
“…In 1998, the World Health Organization (WHO) reported that only in Asia, Africa and America over 200 million Giardia lamblia infections are reported yearly (Macotela et al 2004). Contamination with this pathogenic protozoan leads to malnutrition, diarrhea, nausea, cramps, jaundice, avitaminosis, and weight loss in children (Gadelha et al 2005). The drug of choice in the treatment of giardiasis is metronidazole (Flagyl), which is among the nitroimidazole derivatives and effective on anaerobic bacteria and protozoa.…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, the World Health Organization (WHO) reported that only in Asia, Africa and America over 200 million Giardia lamblia infections are reported yearly (Macotela et al 2004). Contamination with this pathogenic protozoan leads to malnutrition, diarrhea, nausea, cramps, jaundice, avitaminosis, and weight loss in children (Gadelha et al 2005). The drug of choice in the treatment of giardiasis is metronidazole (Flagyl), which is among the nitroimidazole derivatives and effective on anaerobic bacteria and protozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of H. dulcis act as detoxicant in alcohol poisoning and protect the liver against hepatotoxic substances (Kim, 2001;Xu et al, 2003). H. dulcis has medicinal properties, such as antigiardial activity (Gadelha et al, 2005) and others that were reviewed by Hyun et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…To count the number of G. lamblia in culture, researchers frequently use the hemocytometer (Neubauer chamber) (Gadelha et al 2005;Mariante et al 2005;Rayan et al 2005). When dealing with G. lamblia-host cell interaction experiments, the direct use of such chambers is more complicated.…”
Section: Introductionmentioning
confidence: 99%